Promosi kesehatan holistik ibu hamil dan postpartum melalui penguatan kader Posyandu - Ulfah, Diana; Pratidina, Eki; Indarna, Asep Aep; Novianti, Wini Resna (JOURNAL of Public Health Concerns, 2026)
Background: Maternal and postpartum health is a crucial indicator of health development, yet the prevalence of postpartum mental disorders in Indonesia remains high, reaching 20–40%. In Cileunyi Kulon Village, efforts to reduce the Maternal Mortality Rate (MMR) are hampered by limited family understanding and the strong influence of traditional practices on medical and psychological care. Although the family plays a crucial role in successful recovery, the competence of the 27 Posyandu (Integrated Service Post) cadres, the frontline health education providers in this area, is not yet optimal in providing evidence-based health promotion. Therefore, this community service program focuses on strengthening the capacity of cadres through comprehensive family mentoring and education. This strategy aims to improve health literacy and family involvement in maintaining maternal physical and mental well-being, while simultaneously supporting the achievement of SDG point three, related to a healthy and prosperous life. Purpose: To provide technical knowledge regarding perineal wound care and breast care to cadres in an effort to optimize their capacity to become effective facilitators in maintaining maternal physical and mental well-being. Method: Community service was conducted from November 25–28, 2025, in Cileunyi Kulon Village, Cileunyi District, Bandung Regency, involving 42 cadres from 27 Integrated Health Posts (Posyandu) as respondents. Information provided covered perineal wound care, breast care, stress management, and family support. Data were presented descriptively. This community service activity was implemented using a community education and mentoring approach. Results: Based on the results before the educational activity (pre-test), the majority of cadres had poor knowledge, namely 24 people (57.1%), while after the educational activity (post-test), results showed that the knowledge category increased to 15 people (35.7%), and the knowledge category became dominant with 19 people (45.2%). Conclusion: The Posyandu cadre capacity building program in Cileunyi Village significantly improved their understanding of physical and mental health care for pregnant and postpartum women. The increased number of cadres with knowledge after the intervention demonstrates that family health promotion methods effectively equip cadres to be at the forefront of improving maternal well-being in the community. Suggestion: Posyandu cadres are expected to apply the knowledge they have gained in routine service activities, particularly in educating families of pregnant women to create a strong support system at the household level. Keywords: Cadres; Family support; Health promotion; Physical and mental health Pendahuluan: Kesehatan ibu hamil dan pasca persalinan merupakan indikator krusial pembangunan kesehatan, namun prevalensi gangguan mental postpartum di Indonesia masih tinggi mencapai 20–40%. Di Desa Cileunyi Kulon, upaya penurunan Angka Kematian Ibu (AKI) masih terkendala oleh terbatasnya pemahaman keluarga serta kuatnya pengaruh adat dalam perawatan medis dan psikologis. Meskipun peran keluarga sangat menentukan keberhasilan pemulihan, kompetensi 27 unit kader Posyandu sebagai garda terdepan edukasi kesehatan di wilayah ini belum optimal dalam memberikan promosi kesehatan berbasis bukti. Oleh karena itu, program pengabdian masyarakat ini berfokus pada penguatan kapasitas kader melalui pendampingan dan edukasi keluarga yang komprehensif. Strategi ini bertujuan untuk meningkatkan literasi kesehatan serta keterlibatan keluarga dalam menjaga kesejahteraan fisik dan mental ibu, sekaligus mendukung pencapaian SDGs poin ketiga terkait kehidupan sehat dan sejahtera. Tujuan: Memberikan pengetahuan teknis mengenai perawatan luka perineum dan perawatan payudara pada kader sebagai upaya mengoptimalkan kapasitas kader menjadi fasilitator yang efektif dalam menjaga kesejahteraan fisik dan mental ibu. Metode: Pengabdian masyarakat dilaksanakan pada tanggal 25–28 November 2025 di di desa Cileunyi Kulon Kecamatan Cileunyi Kabupaten Bandung dengan melibatkan 42 kader dari 27 Posyandu untuk menjadi responden. Informasi yang diberikan adalah perawatan luka perineum, perawatan payudara, manajemen stres dan dukungan keluarga. Akumulasi data disampaikan secara deskriptif. Kegiatan pengabdian ini dilaksanakan dengan pendekatan pendidikan masyarakat (community education) dan pendampingan. Hasil: Berdasarkan hasil sebelum kegiatan edukasi (pre-test), mayoritas kader memiliki pengetahuan dalam kategori kurang, yaitu sebanyak 24 orang (57.1%), sedangkan setelah kegiatan edukasi (post-test) mendapatkan hasil dengan kategori pengetahuan baik meningkat menjadi 15 orang (35.7%) dan kategori cukup menjadi dominan dengan 19 orang (45.2%). Simpulan: Program penguatan kapasitas kader Posyandu di Desa Cileunyi secara signifikan meningkatkan pemahaman kader mengenai perawatan fisik dan kesehatan mental ibu hamil serta postpartum. Meningkatnya jumlah kader yang memiliki pengetahuan sesudah intervensi membuktikan bahwa metode promosi kesehatan keluarga efektif membekali kader sebagai garda terdepan dalam meningkatkan kesejahteraan ibu di masyarakat. Saran: Para kader Posyandu diharapkan dapat menerapkan pengetahuan yang telah mereka peroleh pada kegiatan pelayanan rutin, khususnya dalam mendidik keluarga ibu hamil untuk menciptakan sistem dukungan yang kuat di tingkat rumah tangga.